READERS’ THEATER: TO IMPROVE STUDENTS READING FLUENCY AND COMPREHENSION - Nopa Yusnilita; Leni Febriantika (Concept : Community Concern for English Pedagogy and Teaching, 2017)
Reader’s Theater is one of the strategies that use as a motivational strategy to promoting fluency and comprehension growth for the students especially. Readers’ theater offers students an opportunity for interpretive oral reading as they use voices, facial expressions, and hand gestures to interpret characters in stories. Readers’ theater builds readers’ confidence, brings stories to life through performance, animates content areas, and improves reading ability, comprehension, and oral reading skills.The objective of this study was to find out whether it is significantly difference on students` reading fluency and comprehension between the students who are taught by using reader theater and those who are not. And to find out the factors that affect the students reading comprehension by using Readers Theater. In doing this research, the writer used experimental method; she used one of pre-experimental designs. The participant in this study is the fourth semester students of English Study Program Baturaja University was 20 students from A.II.1. Based on the finding from statistical analysis, it was found that the mean between posttest and pre-test pair was 19.150,. The value of tobtained was 17.665 which was higher than the ttable (from df (n - 1 = 19) was 17,665. And it could be concluded that the used of Readers’ Theater could improve students’ reading fluency and comprehension. It was seen from the differences between the students’ mean score in pre-test and post-test in which the post-test was higher than pre-test. In implementing the readers’ Theater most of the students along this activities all of the students could played their role, express and enjoy reading the script, and it also could contribute to improvement in students’ reading skill. Key Words: Readers’ Theater, Reading Fluency, and Reading Comprehension